Identification of prosaposin as a neurotrophic factor. - O'Brien, J S (1994)
Prosaposin was identified as a neurotrophic factor stimulating neurite outgrowth in murine neuroblastoma (NS20Y) cells and choline acetyltransferase (ChAT) activity in human neuroblastoma (SK-N-MC) cells. The four naturally occurring saposins, which are derived by proteolytic processing of prosaposin, were tested for activity. Saposin C was found to be active, whereas saposins A, B, and D were inactive as neurotrophic factors. Dose-response curves demonstrated that nanomolar concentrations of prosaposin and saposin C stimulated neurite outgrowth and increased ChAT activity. Prosaposin and saposin C exerted activity by a mechanism independent of nerve growth factor, brain-derived neurotrophic factor, and neurotrophin 3. Binding assays utilizing saposin C as a ligand gave two saturable binding constants, a high-affinity (Kd = 19 pM) and a low-affinity (Kd = 1 nM) constant, with 2000 and 15,000 sites per NS20Y cell, respectively. Phosphorylation stimulation experiments demonstrated that brief treatment with prosaposin or saposin C enhanced phosphorylation of a variety of proteins, some of which contained phosphorylated tyrosine(s). Since both cell lines were also stimulated by ciliary neurotrophic factor (CNTF) as well as prosaposin, inhibition was tested by utilizing an anti-gp130 monoclonal antibody, which specifically inhibited CNTF stimulation; this antibody did not inhibit prosaposin or saposin C stimulation. These results indicate that prosaposin and saposin C are neurotrophic factors which initiate signal transduction by binding to a high-affinity receptor that induces protein phosphorylation.